comportamiento agronómico y valoración nutricional de la asociación brachiaria decumbens con las leguminosas centrosema (Centrosema Pubensis) y kudzu (Pueraria Phaseoloides) en diferentes estados de madurez en el centro experimental la Playita – UTC - Gaibor Aguilar, Ruth Maribel (2013)
This research was conducted on-farm Experimental "La Playita", of the Technical University of Cotopaxi, canton La Maná. The cantonal head of river San Pablo sits on an ancient alluvial terrace of 220 msnm. The research lasted for 120 days of field work, 75 days of experimental work and 45 days of establishment of the trial. In the present study used a design of blocks totally at random, in accordance factorial 2 x 4 taking the two associations, and the four ages of harvest. Three replicates per treatment was used. The simple effect of variable height from floor (cm) Association Brachiaria decumbens Kudzu attained its highest value of 91.36 cm. weight of fodder with the Association Brachiaria decumbens Kudzu reached 2018.52 g. Ages in the single effect on the height of plant 75 days presented its highest value of 149.87 cm. weight of forage to the 75 days showed maximum value with 2177.28 g. The interaction of associations for ages making the heaviest burden of the forage with 2706.48 g. single effect of the leaf weight and weight of stems, reported in the Association Brachiaria decumbens Kudzu with 1211.11 and 605.56 g. in your order. The age recorded the greatest weight of leaf and stem was 75 days with 1415.23 and 653.18 g. in your order. In the interaction, we appreciate that the highest values are recorded in the Association Brachiaria decumbens more centrosema 75 days with weight leaves of 1623, 89g and weight of stems 811.94 g. The length of sheet in the simple fact stands out Brachiaria Association decumbens kudzu 41.38 cm and width of sheet Brachiaria Association decumbens centrosema with 2.40 cm. In the middle ages the greater length of sheet was presented to 75 days with 61.83 cm, in the same way occurred to the width of the sheet with a value of 3.37 cm. Bromatologic study appreciate that as it increases the age of grasses decreases the level of protein, this occurred in both associations both for B. decumbens kudzu who 45 days gets 11.14% protein and 75 days 9.26% protein. In the Association Brachiaria decumbens more centrosema which reported 11.67% to 45 days and 75 days 8.50% protein.